2017
DOI: 10.21873/cgp.20038
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Methylation of T-cadherin Can Be a Diagnostic Biomarker for Colorectal Cancer

Abstract: Abstract. Background/Aim: T-cadherin is a tumor suppressor gene, its predictive value in colorectal cancer (CRC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Canhoroz [15] who measured tissue APN expression also showed that this is not associated with DFS. This study was also limited by the small number of patients recruited [15]. T-cadherin receptor which binds the biologically most active HMW isoform is less well studied but was investigated by Duan et al [16].…”
Section: Adiponectin (Apn)mentioning
confidence: 97%
See 1 more Smart Citation
“…Canhoroz [15] who measured tissue APN expression also showed that this is not associated with DFS. This study was also limited by the small number of patients recruited [15]. T-cadherin receptor which binds the biologically most active HMW isoform is less well studied but was investigated by Duan et al [16].…”
Section: Adiponectin (Apn)mentioning
confidence: 97%
“…However only 58 patients were recruited in this study and their body mass index (BMI) was not known [12]. Canhoroz [15] who measured tissue APN expression also showed that this is not associated with DFS. This study was also limited by the small number of patients recruited [15].…”
Section: Adiponectin (Apn)mentioning
confidence: 99%
“…Because CDH13 promoter methylation is common in many human tumors, it has been suggested as an early detection and prognostic marker for human malignancies [ 27 , 46 , 49 ], particularly colorectal [ 40 , 41 ], breast [ 34 ], and non-small cell lung cancer (NSCLC) [ 29 , 32 , 33 ]. The methylation site, cg02263260, located in the promoter region of CDH13 might be important in assessing breast cancer risk and prognosis [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…[35] In many Asian countries, the incidence of CRC has increased 2 to 4 times over the past few decades. [68] Despite improvements in treatment strategies in recent years, the overall survival rate of CRC is still very low. [8] The survival rate of CRC depends to a large extent on the stage of the disease at the time of diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…[68] Despite improvements in treatment strategies in recent years, the overall survival rate of CRC is still very low. [8] The survival rate of CRC depends to a large extent on the stage of the disease at the time of diagnosis. [9] The 5-year survival rate for CRC patients detected at the local stage is about 90% after curative surgery, 70% for regional patients, and approximately 10% for patients with disseminated disease.…”
Section: Introductionmentioning
confidence: 99%